Temporal association between particulate matter pollution and case fatality rate of COVID-19 in Wuhan - Yao, Ye (Environ Res, 2020)
The coronavirus (COVID-19) epidemic reported for the first time in Wuhan, China at the end of 2019, which has caused 4648 deaths in China as of July 10, 2020. This study explored the temporal correlation between the case fatality rate (CFR) of COVID-19 and particulate matter (PM) in Wuhan. We conducted a time series analysis to examine the temporal day-by-day associations. We observed a higher CFR of COVID-19 with increasing concentrations of inhalable particulate matter (PM) with an aerodynamic diameter of 10 μm or less (PM(10)) and fine PM with an aerodynamic diameter of 2.5 μm or less (PM(2.5)) in the temporal scale. This association may affect patients with mild to severe disease progression and affect their prognosis.